SYSTEMATICS AND IDENTITY OF FOUR PELAGIC SHARKS OF THE FAMILY CARCHARHINIDAE FROM INDIAN REGION - Nair, R V; Appukkuttan, K K; Rajapandian, M E (Indian Journal of Fisheries, 2011)
Four species of pelagic sharks of the family Carcharhinidae belonging to the genera ScoUodon, Loxodon and Rhizoprionodon viz., ScoUodon laticauJus MuUer and Henle, Loxodon macrorhinus MuUer and Henle, Rhizoprionodon (Rhizoprionodon) acutus RuppeJl and Rhizoprionodon (Protozygaena) oUgoUnx Springer which constitute a good fishery along the west and southeast coasts of India are described. Since there is confusion about the systematic position and identity of these species, an attempt is made to give detailed description of all the four species collected from different centres of both the coasts.